Reconceptualisation of Architects’ Intentionality in Computational Form Generation: A Tripartite Model - Duygu Tüntaş Karaman (Footprint)
This paper attempts to create a theoretical framework to reconceptualise architects’ intentionality in computational form generation. Parallel to the increasing complexity of design problems and the increased realm of architects’ responsibility, the last two decades have shown that a vast amount of information can be managed and operated within the design process by using computational methods and associated technologies. This condition led to an expansion of the dominant mode in form computation that largely relies on data-driven forms as outcomes of pure calculations and rationalistic determinism. As an alternative, this study proposes a tripartite model as a basis to understand and assess design intentionality by unfolding and thereby reflecting on designers’ internalised processes. Initially defined in the field of computation, network and communication sciences for management and organisation of information, the proposed model – composed of centralised, partial and distributed approaches – is operational in responding to different forms and degrees of design intentionality within computational processes in architecture.